Emerging Organic Pollutants in Waste Waters and Sludge - Barceló, Damià.; Barceló, Damià. (Water Pollution, 2005)
Over the past fifteen years regulatory agencies have relied on their approaches to characterise and control the release of toxic substances into the aquatic environment: a GC/MS analysis for U.S. EPA designated 126 priority pollutants and 132 dangerous substances according to the European 76/464/CEE Directive and on the bioassays with aquatic bioorganisms. "Emerging Contaminants" correspond in most cases to irregulated contaminants, e.g. surfactants, pharmaceuticals and personal care products (PPCP), or gasoline additives. These two volumes, 5/I and 5/O, of this Handbook deal with the analytical, toxicological and environmental issues of these toxicants. Based on results of up-to-date research they give the reader a balanced view on this rapidly developing and complex subject.